Spontaneous regression of a true intracanalicular fusiform ophthalmic artery anurysm after endovascular treatment of an associated dural arteriovenous fistula - Martínez-Pérez, Rafael (2018)
Ophthalmic trunk aneurysms associated with other vascular malformations are extremely rare, and little is known regarding its natural history and options of treatment. Case Description: We present the interesting case of a 51-year-old man who was admitted with progressive visual loss secondary to a concurrent fusiform ophthalmic trunk aneurysm associated with a dural arteriovenous fistula. He was treated with transarterial embolization of the fistulous point. Conclusions: A follow-up angiogram at 6 months showed complete obliteration of the dural arteriovenous fistula and regression of the ophthalmic trunk aneurysm. The literature is reviewed, and potential pathophysiologic mechanisms leading to this association and regression in this subgroup of aneurysms are discussed.